2013
DOI: 10.1371/journal.pgen.1003531
|View full text |Cite
|
Sign up to set email alerts
|

PARP-1 Regulates Metastatic Melanoma through Modulation of Vimentin-induced Malignant Transformation

Abstract: PARP inhibition can induce anti-neoplastic effects when used as monotherapy or in combination with chemo- or radiotherapy in various tumor settings; however, the basis for the anti-metastasic activities resulting from PARP inhibition remains unknown. PARP inhibitors may also act as modulators of tumor angiogenesis. Proteomic analysis of endothelial cells revealed that vimentin, an intermediary filament involved in angiogenesis and a specific hallmark of EndoMT (endothelial to mesenchymal transition) transforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
125
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(132 citation statements)
references
References 43 publications
6
125
1
Order By: Relevance
“…Furthermore, high PARP-1 expression levels were associated with a larger number of lymph node metastases, suggesting that PARP-1 over-expression increased invasion and metastasis in gastric cancer. Concordant with these results, Rodríguez et al (33) previously demonstrated that inhibition of PARP-1 expression suppressed the invasion and colonization of distal organs in melanoma cells. In addition, Li et al (34) demonstrated that inhibition of PARP expression attenuated the adhesion of mouse colon carcinoma cells to the extracellular matrix and decreased their migration and invasion through Matrigel, suggesting that PARP-1 is important in controlling the migration and invasion of certain cancers.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Furthermore, high PARP-1 expression levels were associated with a larger number of lymph node metastases, suggesting that PARP-1 over-expression increased invasion and metastasis in gastric cancer. Concordant with these results, Rodríguez et al (33) previously demonstrated that inhibition of PARP-1 expression suppressed the invasion and colonization of distal organs in melanoma cells. In addition, Li et al (34) demonstrated that inhibition of PARP expression attenuated the adhesion of mouse colon carcinoma cells to the extracellular matrix and decreased their migration and invasion through Matrigel, suggesting that PARP-1 is important in controlling the migration and invasion of certain cancers.…”
Section: Discussionsupporting
confidence: 68%
“…In addition, Li et al (34) demonstrated that inhibition of PARP expression attenuated the adhesion of mouse colon carcinoma cells to the extracellular matrix and decreased their migration and invasion through Matrigel, suggesting that PARP-1 is important in controlling the migration and invasion of certain cancers. PARP-1 has been previously demonstrated to regulate cell invasion and metastasis through the modulation of epithelial-mesenchymal transition-induced malignant transformation or the regulation of the activity of the nuclear factor kappa-light-chain-enhancer of activated B cells (3336). Further studies are required to determine whether a similar mechanism of PARP-1 occurs in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the invasion and metastasis of melanoma depend on the migration activity and motility of melanoma, which are closely related to cytoskeletal proteins. [86,87] CONCLUSION The significant differences between children and adolescents suggest the existence of age-based inherent differences in the biology of melanoma. Therefore, novel biomarkers that will assist in the diagnosis and prognosis of melanoma need to be developed.…”
Section: Relationship Between Wnt5a/ca 2+ /Calcineurin/ Nuclear Factomentioning
confidence: 99%
“…As melanocytes transform into malignant melanoma cells, Ecadherin expression is lost and vimentin becomes significantly overexpressed [9]. E-cadherin is a cell surface adhesion molecule that plays a critical role in maintaining both the structural integrity of the skin and melanocyte-keratinocyte interaction [10], while vimentin, a mesenchymal filament protein, aids in wound healing, angiogenesis, and cancer growth [11,12]. Studies reveal that primary melanomas overexpressing vimentin and underexpressing E-cadherin tend to have a higher incidence of metastatic disease [9,13].…”
Section: Introductionmentioning
confidence: 99%